Climate and fishing simultaneously impact small pelagic fish in the oceans around the southernmost tip of Africa - Ramírez, Francisco; Shannon, Lynne J.; van der Lingen, Carl D.; Julià, Laura; Steenbeek, Jeroen; Coll, Marta (Frontiers in Marine Science, 2022)
Climate and fisheries interact, often synergistically, and may challenge marine ecosystem functioning and, ultimately, seafood provision and human wellbeing that depend on them. Holistic and integrative approaches aiming at evaluating the spatial overlap between these major stressors are crucial for identifying marine regions and key fish species that require conservation priority to prevent possible future collapses. Based on highly resolved information on environmental conditions and fishing pressure from the Southern Benguela and the Agulhas Bank ecosystems off South Africa, we identified the main areas where small pelagic fish species (European anchovy Engraulis encrasicolus, Pacific sardine Sardinops sagax, and West Coast round herring Etrumeus whiteheadi) have been highly impacted in terms of unfavourable environmental conditions and fishing pressure over the period 1993-2018. We termed these areas cumulative “hotspots” of climate change and fishing impact. We also identified fishing grounds where environmental conditions are now more favourable for these pelagic fish species, terming these “bright spots” of climate change. Environmental conditions and fishing intensity show contrasting patterns between the Southern Benguela and the Agulhas Bank ecosystems, with the Southern Benguela region accumulating most of cumulative hotspots and showing the most negative trends in CPUE (a proxy of local fish abundance). Contrastingly, bright spots, identified on the south coast but also south of Cape Town, showed more positive trends in CPUE, suggesting that they may support sustainable growth of the small pelagic fishery in the medium term. Focussing future fishing effort on these bright spots may serve to alleviate pressure on the doubly and highly impacted cumulative hotspots from the western side of the southernmost tip of Africa.